Pengoptimalan Jaringan Pipa Primer PUDAM Tirtabina Menggunakan Algoritma Greedy - Nabila, Atika; Aprilia, Rima (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Optimization can be defined as the process of finding the best value of a condition that will produce a maximum or minimum value. This research was conducted with the aim of applying the Greedy Algorithm to the optimization of the primary pipe network located in Bilah Hilir District, Labuhanbatu Regency. In the research conducted, the primary pipe will be formed into a weighted graph so that there are 58 edges and 57 points (vertex) with a total length of all pipes of 9,945 meters. In the results of the research conducted, there are two edges that can be removed so as to optimize 850 meters of primary pipes and can optimize costs of 31,450,000. It can be concluded that the pipe reduction is 850 meters from the length of the entire initial pipe, namely 9,945 meters. So, it will automatically reduce the cost of purchasing pipes where the pipe per meter is IDR. 37,000. So the total cost that can be optimized is Rp. 31,450,000 Keywords: Optimization, Primary Pipe, Graph, Greedy Algorithm